Comparative analysis of maize (Zea mays) crop performance: natural variation, incremental improvements and economic impacts. Issue 7 (23rd May 2014) - Leibman, Mark; Shryock, Jereme J.; Clements, Michael J.; Hall, Michael A.; Loida, Paul J.; McClerren, Amanda L.; McKiness, Zoe P.; Phillips, Jonathan R.; Rice, Elena A.; Stark, Steven B.
Summary Grain yield from maize hybrids continues to improve through advances in breeding and biotechnology. Despite genetic improvements to hybrid maize, grain yield from distinct maize hybrids is expected to vary across growing locations due to numerous environmental factors. In this study, we examine across‐location variation in grain yield among maize hybrids in three case studies. The three case studies examine hybrid improvement through breeding, introduction of an insect protection trait or introduction of a transcription factor trait associated with increased yield. In all cases, grain yield from each hybrid population had a Gaussian distribution. Across‐location distributions of grain yield from each hybrid partially overlapped. The hybrid with a higher mean grain yield typically outperformed its comparator at most, but not all, of the growing locations (a 'win rate'). These results suggest that a broad set of environmental factors similarly impacts grain yields from both conventional‐ and biotechnology‐derived maize hybrids and that grain yields among two or more hybrids should be compared with consideration given to both mean yield performance and the frequency of locations at which each hybrid 'wins' against its comparators. From an economic standpoint, growers recognize the value of genetically improved maize hybrids that outperform comparators in the majority of locations. Grower adoption of improved maize hybrids drives increases in average U.S. maize grain yields and contributes significant value to the economy.